Engineering Public Service Excellence for Nunavut: The Nunavut Unified Human Resources Development Strategy - Fortier, Marcel; Jones, Francine Gauthier (ARCTIC, 1998)
In 1999, for the first time since Newfoundland and Labrador joined the Canadian Confederation 50 years ago, the map of Canada will change. A new jurisdiction, called Nunavut, will be carved out of the existing Northwest Territories and officially instituted as Canada's third territory. To a small group of people, the Inuit, the creation of the new territory through the settlement of their land claims is an enormous achievement. Nunavut, which means "Our Land" in Inuktitut, brings increased opportunity to the 24 000 residents of the region, about 85% of whom are Inuit. Nunavut will have a public form of government that respects and reflects Canada's political traditions and institutions, and will remain firmly entrenched within the bonds of Confederation. This public form of government will recognize and protect the political equality of residents regardless of culture, heritage, or beliefs. The Canadian Charter of Rights and Freedoms will protect the rights of all Nunavut citizens. Nunavut will have its own federal member of parliament and its own senator. It will have a nineteen-member, popularly elected Legislative Assembly with a Cabinet and Speaker chosen from among its members.